AutoTAB: An Algorithm to Track Bipolar Magnetic Regions and Initial results from the Tracked BMRs - Sreedevi A.; Jha B.K.; Karak B.B.; Banerjee D. (My University, 2025)
AutoTAB is a state-of-the-art, fully automatic algorithm that tracks the Bipolar Magnetic Regions (BMRs) in magnetogram observations. AutoTAB employs identified BMR regions from Line-of-Sight magnetograms from MDI and HMI (1996–2022) to track the BMRs through their evolution on the nearside of the Sun. AutoTAB enables us to create a comprehensive and unique catalog of tracked information of 9232 BMRs in the mentioned time period. This dataset is used to study the collective statistical properties of BMRs and particularly to identify the correct theory for the BMR formation. Here, we discuss the algorithm’s functionality and the initial findings obtained from the AutoTAB BMRs catalog. © The Author(s), 2024.